Splice variants of lncRNA RNA ANRIL exert opposing effects on endothelial cell activities associated with coronary artery disease. Issue 10 (2nd October 2020) - Cho, Hyosuk; Li, Yabo; Archacki, Stephen; Wang, Fan; Yu, Gang; Chakrabarti, Susmita; Guo, Yang; Chen, Qiuyun; Wang, Qing Kenneth
ABSTRACT: Each gene typically has multiple alternatively spliced transcripts. Different transcripts are assumed to play a similar biological role; however, some transcripts may simply lose their function due to loss of important functional domains. Here, we show that two different transcripts of lncRNA gene ANRIL associated with coronary artery disease (CAD) play antagonizing roles against each other. We previously reported that DQ485454, the short transcript, is downregulated in coronary arteries from CAD patients, and reduces monocyte adhesion to endothelial cells (ECs) and transendothelial monocyte migration (TEM). Interestingly, the longest transcript NR_003529 is significantly upregulated in coronary arteries from CAD patients. Overexpression of ANRIL transcript NR_003529 increases monocyte adhesion to ECs and TEM, whereas knockdown of NR_003529 expression reduces monocyte adhesion to ECs and TEM. Much more dramatic effects were observed for the combination of overexpression of NR_003529 and knockdown of DQ485454 or the combination of knockdown of NR_003529 and overexpression of DQ485454 . The antagonizing effects of ANRIL transcripts NR_003529 and DQ485454 were associated with their opposite effects on expression of downstream target genes EZR, CXCL11 or TMEM106B . Our results demonstrate that different transcripts of lncRNA can exert antagonizing effects on biological functions, thereby providing important insights into the biology of lncRNA. The data further support the hypothesis that ANRIL is the causative gene at the 9p21 CAD susceptibility locus.